Experiences with food insecurity and risky sex among low-income people living with HIV/AIDS in a resource-rich setting - Whittle, Henry J (J Int AIDS Soc, 2015)
BACKGROUND: Forty-nine million individuals are food insecure in the United States, where food insecurity and HIV/AIDS are prevalent among the urban poor. Food insecurity is associated with risky sexual behaviours among people living with HIV/AIDS (PLHIV). No qualitative studies, however, have investigated the mechanisms underlying this relationship either in a resource-rich setting or among populations that include men who have sex with men (MSM). METHODS: Semi-structured in-depth interviews were conducted with 34 low-income PLHIV receiving food assistance in the San Francisco Bay Area. The interviews explored experiences with food insecurity and perceived associations with sexual risk behaviours. Interviews were conducted in English, audio-recorded and transcribed verbatim. Transcripts were coded and analyzed according to content analysis methods using an inductive-deductive approach. RESULTS: Food insecurity was reported to be a strong contributor to risky sexual practices among MSM and female participants. Individuals described engaging in transactional sex for food or money to buy food, often during times of destitution. Participants also explained how food insecurity could lead to condomless sex despite knowledge of and desire to use safe sexual practices, largely because the need to obtain food in the short term was prioritized over the desire to use barrier protection. CONCLUSIONS: Our data extend previous research by demonstrating that food insecurity contributes to transactional and unprotected sex among urban poor individuals in a resource-rich setting, including among MSM. These findings underscore the importance of public health and social intervention efforts focused on structural inequalities.